Influence of Beams Distribution on the Dynamic and Seismic Linear Response of RC Frame Buildings - Silvestri, Stefano; Allahverdiyev, Rovshan; Marconi, Enrico (Frontiers in Built Environment, 2022)
The present study compares the dynamic properties and seismic performances offered by reinforced concrete frame structures characterized by different beams distribution. The understanding of the influence of beams distribution on spatial frames is not only useful when dealing with the seismic vulnerability assessment of existing buildings that may show unusual layouts of beams, such as alternating beams at each storey, but also when facing the design of new buildings with fluid viscous dampers for which some structural flexibility is required. A systematic study is described in this paper. Four (2-, 3-, 6-, and 10-storey) regular frame buildings with rectangular plan are considered as reference structures. Different models are developed according to various layouts of the primary beams, exploring alternatives to the full three-dimensional organisation of beams and frames. For instance: beams placed along the longitudinal direction at the odd storeys and placed along the transversal direction at the even storeys, and vice versa; alternating beams every one and two storeys; beams just placed along one direction. Modal analysis has been conducted to evaluate the influence of beams distribution on the dynamic properties (periods of vibration and modal participating mass ratios). Response spectrum analysis and linear time-history dynamic analysis have been carried out to assess the effects of beams distribution on the fundamental seismic response parameters (shear forces, bending moments, top-storey displacements, interstorey drifts and floor accelerations). On the contrary of what could be expected, the results indicate that structures with beams alternating every storey may show interesting advantages in terms of reduced total base shear, almost comparable bending moments and accelerations, within a still balanced overall behaviour along the two directions, with respect to the complete three-dimensional frame. Two effects are recognized: the period effect and the static scheme effect. The former acting basically on the storey shear forces; the latter acting mainly on the bending moments.